Developing an effective online based training questionnaire for higher education training provider / Nabilah Abdullah ... [et al.] - Abdullah, Nabilah; Ab Malik, Ariff Md; Shaadan, Norshahida; Mohd Lokman, Anitawati (Universiti Teknologi MARA, 2022)
Over close to two decades, many organizations have gradually paved ways for employees to undertake more online training as means of obtaining and renewing knowledge deemed necessary to perform their tasks. The recent Covid-19 pandemic has resulted in many employees having to upskill and reskill not only their IT-related abilities but also on how to communicate, work collaboratively and engage in business differently from usual. Because work must continue, employees need to be continuously educated and trained to ensure they can be effective at work. However, not much is known about online-based training determinants that influence training effectiveness. This study therefore attempts to investigate determinants for effective online-based training (OBT) and develop a questionnaire for effective OBT in higher education setting. The study was conducted in three phases: (i) Phase I – Identification of determinants, (ii) Phase II – Development of questionnaire, and (iii) Phase III – Pilot study. Phase I involved literature analysis using thematic analysis to identify determinants, Phase II involved experts (n=3) and Higher Learning Institution (HLI) staff (n=30) to develop the questionnaire, and Phase III involved a pilot study to test the reliability of the questionnaire. The Cronbach’s Alpha results showed all proposed determinants are consistent and acceptable except Personality Traits and Attitude with only 0.515 and 0.295, respectively. Several steps have been put forward as mechanisms to enhance the overall quality and integrity of the OBT questionnaire. The questionnaire is also expected to provide useful feedback on how OBT sessions can be continuously improved in the future.